Cloud and Precipitation Microphysics Principles and Parameterizations - Straka, Jerry M. (Cambridge University Press, 2013)
The book provides a single source for a combination of the principles and parameterizations, where possible, of cloud and precipitation microphysics. It is not intended to be a comprehensive text on microphysical principles in the spirit of Pruppacher and Klett’s book Microphysics of Clouds and Precipitation. Not every existing parameterization available is included in the book, as this would be an overwhelmingly daunting task, though every effort has been made to include the more common and modern parameterizations.